ANALISIS PREFERENSI SISWA MELANJUTKAN STUDI KE SMPN 1 KABUN KECAMATAN KABUN KABUPATEN ROKAN HULU TP. 2014/2015 - Dewi Purba Dewi Purba; Raja Arlizon Raja Arlizon; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimsto: (a) to analyze aspects ofthe internalfactorsthatbecomethe preferenceof studentschooseSMPN1District ofKabunRokanHulu, (b) to analyze the aspects ofexternal factorswhichbecomethe preferenceof studentschooseSMPN1District ofKabunRokanHulu(c) AnalyzeinternalpreferencecategorystudentschooseSMPN1District ofKabunRokan HuluTA. 2014/2015, (d) Analyze theexternalpreferencecategorystudentschooseSMPN1District ofKabunRokan HuluTA. 2014/2015. The method usedinthisstudyis adescriptivestudy, with atotal samplingtechniquesaturatedsamples. Theresults ofthis study are: (a) Aspects ofthe internalfactorsthatbecomethe preferenceof studentschooseSMPN1District ofKabunTA. 2014/2015islocatedon theindicatorforinterest. (b) aspects of theexternal factorsthatbecomePreferencesstudentschooseSMPN1District ofKabunTA.2014/2015islocatedon theentranceto theSMPwith the approval ofparents. (c) the internalpreferencecategorystudentschooseSMPN1District ofKabunTA. 2014/2015isat the high category, (d) the externalpreferencecategorystudentschooseSMPN1District ofKabunTA. 2014/2015wasin middle category. Keywords: Preferences